2016
DOI: 10.1016/j.scienta.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of resistance on Mangifera indica to Ceratocystis wilt

Abstract: Ceratocystis wilt, caused by Ceratocystis fimbriata is one of the most serious limiting factors for mango production in Brazil. Despite efforts in the selection and the identification of mango cultivars resistant to Ceratocystis wilt, the genetic basis of the resistance remains unknown. Therefore, the objective of this study was to understand the inheritance of resistance to C. fimbriata by artificial inoculations of the pathogen in progenies of six commercial varieties of mango using "Tommy Atkins" as the mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The most common studies on genetic resistance in mango are related to anthracnose diseases (Bally et al, 2013), powdery mildew (Naqvi et al, 2014), mango malformation (Chakraborti and Misra, 2014), and mango wilt (Arriel et al, 2016). Works that evaluate resistance to dieback disease in mango, caused by fungi of the family Botryosphaeriaceae, are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common studies on genetic resistance in mango are related to anthracnose diseases (Bally et al, 2013), powdery mildew (Naqvi et al, 2014), mango malformation (Chakraborti and Misra, 2014), and mango wilt (Arriel et al, 2016). Works that evaluate resistance to dieback disease in mango, caused by fungi of the family Botryosphaeriaceae, are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the selection of genotypes that show resistance to the development of the dieback disease of mango branches presumably reduce the endophytic and sequential development of these fungi from the mature branch to the inflorescence and pedicel (Johnson et al, 1992), consequently reducing stem-end rot. Arriel et al (2016) evaluated the inheritance of resistance to C. fimbriata in 197 mango genotypes from six families and reported that cultivars Keitt and Tommy Atkins were the most resistant, and cultivars Espada and Haden were the most susceptible to mango wilt. In the present study, cultivars Keitt, Haden, and Espada showed absence of symptoms higher than 94% in branches inoculated with L. theobromae, and 100% absence of symptoms in the material Batista et al (2012) reported that fruits of the 'Tommy Atkins' variety showed susceptibility to stem-end rot caused by N. parvum and F. aesculi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some rootstocks are able to buffer the trees against saline and calcareous soils and poor quality irrigation waters (Kadman et al, 1976;Gazit and Kadman, 1980;Pandey et al, 2014). There are others that are resistant to diseases such as mango wilt caused by the fungus Ceratocystis fimbriata (Rossetto et al, 1997;Arriel et al, 2016). In studies conducted in northern Australia with rootstocks from 95 poly-embryonic cultivars there was no clear relationship between dwarfing in the field and the vigour of the trees in the nursery (Bithell et al, 2016).…”
Section: Dwarfing Rootstocks and Interstocks Used To Control Tree Sizementioning
confidence: 99%